2005
DOI: 10.1590/s0101-20612005000100022
|View full text |Cite
|
Sign up to set email alerts
|

Extração aquosa enzimática de óleo de soja

Abstract: -INTRODUÇÃOA industrialização da soja no Brasil, coincidindo com a expansão da produção, iniciou-se na década de 50, nas pequenas empresas que se dedicavam ao esmagamento de outras oleaginosas, nos Estados da região Sul e em São Paulo [11]. Desde os anos 60, a quantidade produzida vem crescendo tão aceleradamente que, nos últimos anos, o país ocupa a segunda posição como produtor mundial dessa oleaginosa [15].Os processos industriais normais utilizados na produção de óleo consistem de prensagem contínua ou hid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…According to Rosenthal et al (2001), the use of Alcalase 2.4L (protease) increased the oil yield from heat-treated soybean flour as compared to cellulase, hemicellulase, and pectinase. Similarly, Santos and Ferrari (2005) reported that both Alcalase and Celluclast (cellulase) were able to increase the oil yield from soybeans, with Alcalase giving higher yields. A higher yield in the case of protease (96.0%) as compared to phospholipase (73.4%) was also reported by Jung, Maurer, and Johnson (2009) in the case of extruded soybean flakes.…”
Section: Aqueous Enzymatic Extraction (Aee) Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…According to Rosenthal et al (2001), the use of Alcalase 2.4L (protease) increased the oil yield from heat-treated soybean flour as compared to cellulase, hemicellulase, and pectinase. Similarly, Santos and Ferrari (2005) reported that both Alcalase and Celluclast (cellulase) were able to increase the oil yield from soybeans, with Alcalase giving higher yields. A higher yield in the case of protease (96.0%) as compared to phospholipase (73.4%) was also reported by Jung, Maurer, and Johnson (2009) in the case of extruded soybean flakes.…”
Section: Aqueous Enzymatic Extraction (Aee) Methodsmentioning
confidence: 93%
“…According to Jiang et al (2010), Abdulkarim et al (2006), Santos and Ferrari (2005), and Dominguez et al (1996), degradation of cell wall components can be enhanced by prolonging the incubation time. Passos et al (2009) also reported that the use of an enzyme mixture of cellulase, protease, xylanase, and pectinase for 120 h resulted in 3.8% higher yield as compared to 24 h of incubation time.…”
Section: Incubation Timementioning
confidence: 99%
See 2 more Smart Citations
“…Alcalase ® 2.4L is an endoprotease used in many extraction processes. Santos and Ferrari33 used the protease Alcalase and a cellulase for the aqueous enzymatic extraction of soybean oil, and the protease showed better extraction efficiency. However, in the lysis of the C. necator cell wall, it was observed that Alcalase ® 2.4L provided a statistically lower extraction (83.1%) than the enzyme composed of cellulase (Celumax ® BC).…”
Section: Resultsmentioning
confidence: 99%